FORECASTING THE PRODUCTION OF GROUNDNUT IN TURKEY USING ARIMA MODEL - S. Celik; K. Karadas; E. Eyduran (Journal of Animal and Plant Sciences, 2017)
The aim of this study was to model groundnut production in Turkey using data from the period 1950- 2015 in Turkey in an effort to forecast groundnut production amounts between the years 2016 and 2030 by using Autoregressive Integrated Moving Average (ARIMA) models. In the study, ARIMA (0,1,1) was found to be the most appropriate model among six studied ARIMA models in forecasting the groundnut production amounts for the next 15 years. We forecasted that annual amount of groundnut production obtained in the year 2016 was 138,98 thousand tons and it reached to 167,28 thousand tons in the year 2030 with a significant acceleration for groundnut production. Forecasting results of the ARIMA (0,1,1) illustrated an increasing trend in the amount of groundnut production, and they might help to determine a better policy for increasing groundnut production in Turkey.
Keywords: ARIMA; Groundnut Production Forecasting; Time Series Models; Autocorrelation Function; Partial Autocorrelation Function; Production Planning and Control.